Transformation of MSMEs as a Local Economic Convergence Engine: A Community Service Model Based on Digitalization, Financial Inclusion, and Sustainable Regional Development Spillover - Daniel Ebenezer Silaban; Simon Patar Rizki Manalu; Budi Artaman Lase; Nabilah Pratiwi; Erlinisati Putri Melati Gulo (Green Publisher Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economy, contributing over 60% to GDP and absorbing nearly 97% of the workforce. Despite this significant contribution, MSMEs face challenges such as low digital literacy, limited access to formal financing, and unequal regional development, which hinder economic convergence and inclusive growth. Addressing these issues is critical in the context of an increasingly digital and interconnected economy. This study aims to design a transformation model for MSMEs as engines of local economic convergence through digitalization, financial inclusion, and sustainable regional development spillovers. Employing a community-based participatory research approach, the study integrates data from Statistics Indonesia, the Ministry of Cooperatives and SMEs, Bank Indonesia, and the Financial Services Authority. A purposive sample of 250 MSMEs was selected to represent varying levels of digital adoption, financial access, and geographic distribution. Data were collected using structured questionnaires, interviews, and secondary sources, with validity and reliability ensured through expert review and Cronbach’s alpha analysis. Data analysis employed descriptive, comparative, and interpretative techniques to evaluate pre- and post-intervention outcomes. The results indicate that MSME digitalization accelerates market, income, and spatial convergence, while financial inclusion supports sustainable growth but remains unevenly distributed. The implementation of the Integrated MSME Convergence Model (IMCM) generates regional spillover effects, including increased demand for local inputs, expanded distribution networks, job creation, and knowledge transfer. These outcomes demonstrate that MSMEs, when supported by integrated policies and digital infrastructure, can function as strategic agents of regional development. In conclusion, the study confirms the potential of digitalized and financially included MSMEs to promote inclusive and sustainable economic growth, highlighting the need for coordinated policy interventions and continuous community-based support.